2000
DOI: 10.1038/sj.jea.7500074
|View full text |Cite
|
Sign up to set email alerts
|

Residence location as a measure of environmental exposure: a review of air pollution epidemiology studies

Abstract: Residence location has long been used to indicate environmental exposure in many epidemiological studies. This indicator is easy to establish, requires little exposure or monitoring data, and is potentially applicable to many types of investigations. The validity, accuracy and utility of residence location as an exposure indicator, however, is challenged by current concerns regarding multiple exposure pathways, persistent and toxic contaminants, and cumulative exposures from non -point, mobile and point source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(52 citation statements)
references
References 68 publications
2
49
0
1
Order By: Relevance
“…Recently, the use of residence as an indicator of exposure in air pollution epidemiology has been criticized, mostly because the used indicators of exposure based on residence such as distance to a source do not necessarily reflect the true spatial pattern of exposure (Huang and Batterman, 2000 ). Most of the criticisms do not apply to the current study.…”
Section: Limitations Of the Methodsmentioning
confidence: 94%
“…Recently, the use of residence as an indicator of exposure in air pollution epidemiology has been criticized, mostly because the used indicators of exposure based on residence such as distance to a source do not necessarily reflect the true spatial pattern of exposure (Huang and Batterman, 2000 ). Most of the criticisms do not apply to the current study.…”
Section: Limitations Of the Methodsmentioning
confidence: 94%
“…Previous research has demonstrated that personal exposures typically correlate more strongly with indoor levels, especially in homes with combustion sources (Levy, 1998 ). However, epidemiologic studies frequently use outdoor NO x or NO 2 concentrations, or housing characteristics (distance of residence from highway or traffic density ), to estimate or classify exposure ( Jaakkola et al, 1991;Dockery et al, 1993;Nitta et al, 1993;Nicolai, 1997;Asgari et al, 1998;Jammes et al, 1998;Guo et al, 1999;Huang and Batterman, 2000 ). These methods fail to account for the significant contribution of indoor sources to personal exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Huang and Batterman ( 2000 ), in a recent review of 45 epidemiological studies that used residence location as a measure of exposure to air pollution, recommend the use of modeling to reduce exposure misclassification that leads to nonsignificant findings.…”
Section: Discussionmentioning
confidence: 99%